Demographic Characteristics of International Travelers Visiting Travel Clinics in Saudi Arabia: A Cross-Sectional Study - Mohammed Alzhrani, Abdalgader; Alzharani, Fahad Abdullah; Abd-Ellatif, Eman Elsayed; Alkulaib, Faisal Khalid; Alotaibi, Adel Fahad (Journal of Neonatal Surgery, 2025)
Background: The rise in international travel presents public health challenges, especially in infectious disease transmission. Travel clinics mitigate these risks through vaccinations, prophylaxis, and counseling. This study explores traveler demographics, the most frequently required services, and the relationship between travel-related factors and service utilization in Saudi Arabian clinics. Methods: This cross-sectional study analyzed data from 1,807 international travelers who visited travel clinics in Saudi Arabia from January to December 2023. Data were obtained from the Communicable Disease Control General Department’s records. Demographic variables included age, gender, nationality, occupation, and travel-related factors. Statistical analyses were performed using SPSS, including descriptive statistics and logistic regression models. Results: Most travelers were male (74.3%) with a median age of 35 years. The most frequent age group was 18–39 years (54.6%). Saudi and non-Saudi nationals were nearly equally represented. White-collar workers comprised 36.1%, and Africa was the main destination (69.7%). Work was the primary travel purpose (37.4%), followed by tourism (32.6%). The most frequent travel duration was one month (38.1%), with peak travel in July. Vaccinations were the most utilized service (90.3%), with yellow fever being the most common vaccine (73.6%). Gender, nationality, age, and region were significantly associated with vaccination and prophylaxis use. Conclusion: This study reveals key demographic patterns among travelers, with a predominance of male, work-related travel, and high vaccination uptake. Findings emphasize the necessity for customized travel health services to strengthen public health measures and curb disease spread.